Changing the subject : a theory of rhetorical empathy - Blankenship, Lisa, 1970- (Utah State University Press, An imprint of University Press of Colorado, 2019)
This book explores ways of engaging across difference by studying the concept of empathy from a rhetorical perspective. The book considers how empathy can be a deliberate, conscious choice to understand others through listening and exploration of pathos. The book also explores how language and symbol systems play in this process that is cognitive and affective. -- Publisher's description.